Prediction of potential inhibitors against SARS-CoV-2 endoribonuclease: RNA immunity sensing - Al-Rashedi, Nihad A. M. (J Biomol Struct Dyn, 2020)
The World Health Organization has classified the COVID-19 outbreak a pandemic which is caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) and declared it a global health emergency. Repurposing drugs with minimum side effects are one approach to quickly respond in attempt to prevent the spread of COVID-19. SARS-CoV-2 encodes several RNA processing enzymes that are unusual and unique for single-stranded RNA viruses, including Nsp15, a hexameric endoribonuclease that discriminatory cleaves immediately 3′ of uridines. The structure of SARS-CoV-2 Nsp15 is reported to be homologous to that of the Nsp15 endoribonucleases of SARS-CoV and MERS-CoV, but it exhibits differences that may contribute to the greater virulence of SARS-CoV-2. This study aimed to identify drugs that targeted SARS-COV-2 Nsp15 using a molecular docking-based virtual screening of a library containing 10,000 approved and experimental drugs. The molecular docking results revealed 19 medications that demonstrated a good ability to inhibit Nsp15. Among all the candidated 19 drugs only five FDA approved drugs were used for further investigation by molecular dynamics simulation, the stability of Nsp15-ligand system was evaluated by calculating the RMSD, RMSF, radius of gyration and hydrogen bond profile. Furthermore, MM-PBSA method was employed to validate the binding affinity. According to the obtained results of MD, the complex of Olaparib was showed more stability and lower binding free energy than the control inhibitor during MD simulation time. Finally, we suggest that Olaparib is a potential drug for treating patients infected with SARS-CoV-2 and provide insight into the host immune response to viral RNA. Communicated by Ramaswamy H. Sarma